Knowledge and attitude about risky pregnancy among student - Suci Musvita Ayu; S. Lindawati; Thoharoh Halimatusa’diyah (Institute of Advanced Engineering and Science, 2020)
This study was conducted examine the effect of counseling on the increasing knowledge and attitudes about risky pregnancies at Muhammadiyah 1 Vocational High School in Wonosobo, Indonesia. This research was quasi-experimental research employed quasi experiment design with one group pretest-post-test design. Measurements were made before and after treatment, by doing a pre-test and post-test. Sample sie in this study was 108 students. The instrument in this study is the questionnaire. The results of the knowledge variable showed a significant value 0.003. There is an effect of reproductive health counseling on increasing knowledge and attitudes about risky.